Doped Diamond: A Compact Review on a New, Versatile Electrode Material - Alexander Kraft (International Journal of Electrochemical Science, 2007)
The present paper gives an overview on the current development status of doped-diamond electrodes for electrochemical applications. It starts with a short discussion on the different types of diamond electrodes and their preparation methods. This is followed by a summary of the electrochemical properties of diamond electrodes in different electrolytes. Modification strategies for doped-diamond electrodes are discussed as an important technology to change their electrochemical properties. The second part of the paper deals with practical applications of diamond electrodes from water treatment to inorganic and organic electrosynthesis, electroanalysis and electrochemical energy technology to biotechnology.